Fenomena Klitih Utopia Sosialis dalam Perspektif Edward Bellamy - Hari Suciyanto Wibowo; Victor Novianto; Kristina Warniasih (Program Magister Pendidikan IPS UPY, 2026)
Yogyakarta's reputation as a cultural city, student city, and tourist destination does not exempt it from acts of criminality. The increasingly rampant phenomenon of klitih, particularly in the Yogyakarta area, is a transformation of a local term that originally had a positive meaning but has now shifted into a form of street violence committed by youths. This article aims to examine klitih within the context of social reality and connect it to the socialist utopian perspective of Edward Bellamy. Klitih is viewed as a reflection of social failure in educating and shaping the character of adolescents, triggered by weak family control, social environment, and educational institutions. Through a descriptive-qualitative approach and literature review, this article identifies the driving factors behind klitih, including adolescent identity crises, poor parenting patterns, character-deficient education, and negative environmental influences. Within Bellamy's conceptual framework, solutions to the klitih phenomenon must be based on social transformation to eliminate inequality, build solidarity, and strengthen social institutions such as families, schools, and communities. Preventive strategies can be implemented through schools by emphasizing character education, and through active roles of families, law enforcement, and communities that support the healthy and just development of adolescents. Thus, addressing klitih requires collaborative efforts from all parties so that its occurrence can be minimized, or even eliminated.